2018
DOI: 10.1007/s11079-017-9452-1
|View full text |Cite
|
Sign up to set email alerts
|

The Size of the Rental Market and Housing Market Fluctuations

Abstract: The paper investigates whether the size of the rental market affects house prices fluctuations or the volatility of construction sector activity over the business cycle. For that purpose we construct a database of variables describing the housing sector in a group of twelve initial euro area members and ten other OECD countries over the years 1995-2014 and conduct a series of panel regressions. We find that a developed rental market attenuates fluctuations in the housing sector, especially for the common curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 33 publications
1
21
0
2
Order By: Relevance
“…First, we added the housing market as the sixth institutional area in the set of basic research categories. The global financial and economic crisis has vividly shown that there exists a very strong link between general economic conditions and the state of the housing market as well as between the housing market condition and its institutional surrounding [Czerniak and Rubaszek, 2018]. It may be argued therefore that the organization of the residential market should be explicitly included in the research agenda as the sixth institutional area for discriminating between different types of capitalism in CEE11 countries.…”
Section: Methodsmentioning
confidence: 99%
“…First, we added the housing market as the sixth institutional area in the set of basic research categories. The global financial and economic crisis has vividly shown that there exists a very strong link between general economic conditions and the state of the housing market as well as between the housing market condition and its institutional surrounding [Czerniak and Rubaszek, 2018]. It may be argued therefore that the organization of the residential market should be explicitly included in the research agenda as the sixth institutional area for discriminating between different types of capitalism in CEE11 countries.…”
Section: Methodsmentioning
confidence: 99%
“…To ensure rationality, the items were mainly adapted from previous studies. In this study, the construct of PU1 was adopted from Czerniak [3], Zhou [34] and Davidson [69], and evaluated through three items of PU11-PU13. Items for PU2 were adapted from Zhou and Fisher [40,70].…”
Section: Questionnairesmentioning
confidence: 99%
“…China's homeownership rate is higher than those of developed countries or regions, which are mostly around 65%. In terms of the leasing rate, Germany, for instance, has reached more than 45% [3]. The leasing and purchasing markets in China are severely out of balance.…”
Section: Introductionmentioning
confidence: 99%
“…This result is confirmed by an empirical study by Cuerpo et al (2014), who indicate that private rental market regulations, in particular different aspects of rent controls and tenant-landlord regulations, influence the response of house prices to economic and demographic disturbances. Similarly, Czerniak and Rubaszek (2016) find that the size of the rental market has a significant impact on house prices fluctuations and the variability in the construction sector activity in the euro area economies. Finally, a number of studies find that an increase in the availability of rental housing leads to higher population mobility, hence to more efficient allocation of the labor force (Barcelo, 2006;Caldera-Sanchez and Andrews, 2011).…”
Section: Introductionmentioning
confidence: 86%